Serum selenium levels in brucellosis - Zeki Aras; Uçkun Sait Uçan (Eurasian Journal of Veterinary Sciences)
In this study. 29 human serum samples from Van (Başkale) province and 12 cattle serum samples from Konya were used. Titer determination ol brucella positive serum samples was carried out using Serum Agglutination Tesl pre-ceeded by Rose Bengal Plale Test. Serum trace element concentrations were determined by ICP-AES, There were significant differences between serum selenium levels of the healthy and diseased human as well as cattle. Serum Selenium levels in healthy groups of human and Cattle were found 59.85 + 1.94 mg/L ve 2 .58 + 0.25 mg/L, respectively while corresponding levels in the diseased groups 36.18+ 1.94 mg/L and 1.35 ±0.12 mg/L (p<0.05).